Psychometric Properties of Farsi Version of the Wish to be Dead Scale. (November 2017) - Dadfar, Mahboubeh; Lester, David; Atef Vahid, Mohammad Kazem; Abdel-Khalek, Ahmed M.
The Wish to be Dead Scale (WDS) is a new scale to measure precursors to suicidal ideation, and the aim of the present study was to examine the psychometric characteristics of a Farsi version of the WDS. The sample was a convenience sample of 145 Iranian female undergraduates and postgraduates selected from different faculties at Iran University of Medical Sciences, Iran. Using a principal component analysis and a varimax rotation with Kaiser normalization, three factors were identified and labeled: (a) lack of purpose and usefulness in life, (b) lack of interest in living, and (c) fantasizing about being dead. The WDS had good inter-item and test–retest reliability and significant positive correlations with scores on the Kessler Psychological Distress Scale-10 and the Rosenberg Self-Esteem Scale, and negative correlations with scores on the Adult Hope Scale, the Satisfaction with Life Scale, the General Self-Efficacy Scale, the Love of Life Scale, the Life Orientation Test, and the Oxford Happiness Questionnaire. We conclude that the WDS may prove to be useful in clinical practice and research into suicide.